End-of-Life Practices Among Tertiary Care PICUs in the United States: A Multicenter Study. Issue 7 (September 2015) - Meert, Kathleen L.; Keele, Linda; Morrison, Wynne; Berg, Robert A.; Dalton, Heidi; Newth, Christopher J. L.; Harrison, Rick; Wessel, David L.; Shanley, Thomas; Carcillo, Joseph; Clark, Amy; Holubkov, Richard; et al.
Abstract : Objective: To describe variability in end-of-life practices among tertiary care PICUs in the United States. Design: Secondary analysis of data prospectively collected from a random sample of patients ( n = 10, 078) admitted to PICUs affiliated with the Collaborative Pediatric Critical Care Research Network between December 4, 2011, and April 7, 2013. Setting: Seven clinical centers affiliated with the Collaborative Pediatric Critical Care Research Network. Patients: Patients included in the primary study were less than 18 years old, admitted to a PICU, and not moribund on PICU admission. Patients included in the secondary analysis were those who died during their hospital stay. Interventions: None. Measurements and Main Results: Two hundred and seventy-five (2.7%; range across sites, 1.3–5.0%) patients died during their hospital stay; of these, 252 (92%; 76–100%) died in a PICU. Discussions with families about limitation or withdrawal of support occurred during the initial PICU stay for 173 patients (63%; 47–76%; p = 0.27) who died. Of these, palliative care was consulted for 67 (39%; 12–46%); pain service for 11 (6%; 10 of which were at a single site); and ethics committee for six (3%, from three sites). Mode of death was withdrawal of support for 141 (51%; 42–59%), failed cardiopulmonary resuscitation for 53 (19%; 12–28%), limitation of support for 46 (17%; 7–24%), and brain death for 35 (13%; 8–20%); mode of death did not differ across sites ( p = 0.58). Organ donation was requested from 101 families (37%; 17–88%; p < 0.001). Of these, 20 donated (20%; 0–64%). Sixty-two deaths (23%; 10–53%; p < 0.001) were medical examiner cases. Of nonmedical examiner cases ( n = 213), autopsy was requested for 79 (37%; 17–75%; p < 0.001). Of autopsies requested, 53 (67%; 50–100%) were performed. Conclusions: Most deaths in Collaborative Pediatric Critical Care Research Network–affiliated PICUs occur after life support has been limited or withdrawn. Wide practice variation exists in requests for organ donation and autopsy.